PSYCHOLOGICAL FACTORS AFFECTING STUDENT’S IN ORAL PRESENTATION AT THE ENGLISH EDUCATION OF UNIVERSITAS ISLAM MAKASSAR - Sari, Sindi Rafika; khalik, Muh. Fihris; Sulviana, Sulviana (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2025)
The purpose of this research is to find out the psychological factors in students’ in conducting oral presentations using English in Universitas Islam Makassar. The research method used is the researcher will use a descriptive research design. Descriptive research is a type of research that systematically describes the situation and facts of a particular population factually and accurately. This design will be used to find out the psychological problems faced by English Department students in making oral presentations. The research sample for this researcher is English language education student’s class 2023 at Universitas Islam Makassar consisting of 1 class with a total of 9 students consisting of 7 female students and 2 male students. Factors affecting students in speaking may vary considerably, depending on the research context. The present study therefore attempts to find out the inhibited psychological factors faced by English Language Department Students and find ways to minimize these factors so that they do not happen to students. Researchers used a qualitative descriptive approach and applies the purposive sampling technique, In this research, research chose subjects according to the needs and objectives of the research. Researcher conducted research on English education students, especially the class of 2023 at the Universitas Islam Makassar. Data collected through observation checklists and interview. The results showed that fear of mistakes, shyness, anxiety, and lack of confidence were the four physiological factors found on students. Meanwhile, other factors that may or may not affect the students well be critically examined. The ways to solve the psychological factors faced by the students in doing presentation are giving motivation the students and stimulation to practice in doing presentation.